Stained Glass Windows of the Church of Christ the King in Gliwice. Iconography and Restoration - KOMAR Beata (Architecture, Civil Engineering, Environment)
In Silesia at the turn of the 19th and 20th centuries and the interwar period, the most important in the production of glass, and thus stained glass, were German factories, among which the Josephinehütte in Szklarska Poręba, known not only in Europe, was the leader. In the Church of Christ the King in Gliwice, you can see stained glass windows by two German studios: Franz Mayer, Hofkunstanstalt & Glasmalerei from Munich and August and Jan Wagner from Berlin-Trepetow, also known as Puhl & Wagner, Gottfried Heinersdorff. The aim of the article is to present the stained glass windows of both studios and to fill the research gap regarding their activities in Gliwice. The article was created on the basis of an archival query in the parish archives, literature analyses, in situ research, interviews in the stained glass workshop and extremely valuable correspondence with an employee of Franz Mayer’s company. As a result of the conducted analyses, the icono-graphic material of all stained glass windows was obtained, the process of their renovation was familiarized and their current condition was assessed.